2016
DOI: 10.3892/or.2016.4590
|View full text |Cite
|
Sign up to set email alerts
|

ST6GalNAcII mediates tumor invasion through PI3K/Akt/NF-κB signaling pathway in follicular thyroid carcinoma

Abstract: Abstract. Altered sialylation, closely associated with tumor progression and metastasis, has been implicated in human thyroid carcinoma. The present study investigated the alteration in expression of ST6GalNAcII involved in invasion and to clarify the possible mechanism of ST6GalNAcII in the metastasis process in human follicular thyroid carcinoma cell lines. Using real-time PCR, western blot and IHC analysis, ST6GalNAcII differed in three follicular thyroid cancer cell lines (FTC133, primary and FTC238, lung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…However, little is known regarding the relationship between ST6GALNAC2 and chemoresistance in CRC. ST6GALNAC2 was identified down‐regulated in follicular thyroid carcinoma and breast cancer, and the differential expression was in accordance with our current results. ST6GALNAC2 expressed a lower level in CRC tissues and 5‐FU‐resistant CRC cell lines.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, little is known regarding the relationship between ST6GALNAC2 and chemoresistance in CRC. ST6GALNAC2 was identified down‐regulated in follicular thyroid carcinoma and breast cancer, and the differential expression was in accordance with our current results. ST6GALNAC2 expressed a lower level in CRC tissues and 5‐FU‐resistant CRC cell lines.…”
Section: Discussionsupporting
confidence: 91%
“…Over‐expressed molecules of PI3K/AKT pathway, caused by aberrant sialylation, resulted in the evolution of AML . ST6GALNAC2 played a crucial role in the procession of follicular thyroid carcinoma and breast cancer via PI3K/AKT pathway. Surprisingly, sufficient evidence has been provided that miRNAs could modulate the activity of PI3K/AKT pathways .…”
Section: Discussionmentioning
confidence: 99%
“…ST6GALNAC2 regulates breast cancer invasion 40 , 41 . In FTC research, we found that ST6GALNAC4 and ST6GALNAC2 modulate tumourigenicity of FTC 17 , 42 and that miR146a/b promotes FTC cell proliferation via the inhibition of ST8SIA4 16 . In the current study, ST6GAL2 was more highly expressed in FTC tissues and cell lines compared with normal tissues and cell lines.…”
Section: Discussionmentioning
confidence: 96%
“…A xenograft of FTC-238 cells with silenced ST6GalNAc2 showed lower tumor volume in mice, as compared with the control FTC-238 xenograft. Overexpression of ST6GalNAc2 in the FTC-133 non-invasive cell line enhanced its invasive ability and increased the tumor volume in xenograft mouse [ 104 ].…”
Section: Glycosylation In Thyroid Pathologymentioning
confidence: 99%